(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Plants form the main part of the environment that surrounds us and has becomes the prime source of medicine and food since time immemorial. Ayurveda has always approached health in both preventive and curative aspect which itself is the main principle of Ayurveda, to maintain the health of a healthy individual, and to overcome the diseases in a person suffering from illness. Diseases pertaining to general health as well as a specific system -targeted diseases have become prevalent in the recent years. Among this a grave increase in the diseases affecting the respiratory system has been noted. Poor air quality, prevalence of antibiotic-resistant microorganisms, newer generations of virulent viruses have all proved to be the possible cause. Recent years witnessed the emergence of Covid pandemic which claimed the life of millions across the world. Even today, many variants of the virus can be seen detected. Diseases affecting the respiratory system drastically affect the persons general immunity and quality of life. Among the medicinal interventions put forward by various health systems to combat the air borne pathogens and diseases, Ayurvedic single and compound formulations proved to significantly useful. Panalveradi kwatha is one such formulation mentioned in the text Sahasrayogam which is commonly used by physicians of South India to combat side effects of respiratory infections as well as respiratory diseases like bronchitis, bronchial asthma. This article is intended to explore the pharmacological potential of Panalveradi Kwatha in the treatment of diseases pertaining to the upper and lower respiratory tract.